The impact of cert-mania on English language learning and teaching: The cypriot case - Tsagari, Dina; Giannikas, Christina N. (My University, 2021)
Language certification has attracted a lot of attention among practitioners, researchers and policy makers in educational contexts around the globe. Given the emphasis placed on certificates in language education, the present study sets out to investigate the impact of language certification on English language teaching and learning in the Cypriot context taking into consideration teachers’ perspectives. The participating teachers were encouraged to reflect on the nature of high-stakes language examinations operating in the local system and the effect of language certification on learning and teaching via an online survey. The teachers were also asked to voice their opinions on issues of examination policy, and the demands of certification on their profession. The paper presents the results and discusses the impact of certification within the educational system of Cyprus and beyond. It concludes by emphasising the need for establishing teacher-support mechanisms that can help increase teachers’ Language Assessment Literacy (LAL) and minimise the washback effect of testing and certification on foreign language teaching and learning.
Keywords: High-stakes language exams; Language Assessment Literacy (LAL); Language certification; Washback